How to fight rural poverty in Uzbekistan? - Shadikhodjaev, Uygun Shuhratovich (KDI School, 2011)
In this work I try to evaluate extent of poverty, specifically rural poverty in Uzbekistan, a former Soviet Republic. By comparing data for poverty by making linear regression and computing forecasted poverty rate I find that actual poverty is lower than forecasted. Therefore, the focus moves to rural poverty and to fight it and author tries to implement Lewis two sector model to fight against rural poverty. Finally, various policy recommendations are drawn after careful analysis of rural poverty.
Thesis(Master) --KDI School:Master of Public Policy and Management,2011